Ragam Praktik Kebijakan Perlindungan Keselamatan Angkutan Sewa Khusus Terkini di Seluruh Dunia - Nur Muhamad Iqbal; Reza Fathurrahman (Program Studi Administrasi Negara Universitas Serang Raya, 2024)
The issuance of Permenhub RI Number 12 of 2019 encourages various two-wheeled special rental transportation companies (also known as online transportation or ride-hailing), to carry out coaching, supervision, and compliance with traffic safety. This article explores the implementation of safety protection policies for specific rental transport users around the world as a benchmark based on a literature review on the Scopus database in the 2015-2023 publication year. The results of the thematic analysis identify five categorization issues: Driver safety, passenger safety, company/operator obligations, transportation policies, and factors causing accidents. The results of the analysis found that the main cause of accidents in special rental transportation is fatigue caused by the absence of a maximum limit of passengers that drivers can serve every day. In addition, special rental transport drivers are considered inadequate due to lack of driving experience, limited participation in traffic safety education, and low awareness of safety education and information.